Synergistic Protective Activity of Tumor-Specific Epitopes Engineered in Bacterial Outer Membrane Vesicles - Grandi, Alberto; Tomasi, Michele; Zanella, Ilaria; Ganfini, Luisa; Caproni, Elena; Fantappiè, Laura; Irene, Carmela; Frattini, Luca; Isaac, Samine J.; König, Enrico; Zerbini, Francesca; Tavarini, Simona; et al. (Frontiers in Oncology, 2017)
Introduction Bacterial Outer Membrane Vesicles (OMVs) are naturally produced by all Gram-negative bacteria and thanks to their plasticity and unique adjuvanticity are emerging as an attractive vaccine platform. To test the applicability of OMVs in cancer immunotherapy we decorated them with either one or two protective epitopes present in the B16F10EGFRvIII cell line and we tested the protective activity of OMV immunization in C57BL/6 mice challenged with B16F10EGFRvIII. Materials and methods The 14 amino acid B cell epitope of human epidermal growth factor receptor variant III (EGFRvIII) and the mutation-derived CD4+ T cell neo-epitope of kif18b gene (B16-M30) were used to decorate OMVs either alone or in combination. C57BL/6 were immunized with the OMVs and then challenged with B16F10EGFRvIII cells. Immunogenicity and protective activity was followed by measuring anti-EGFRvIII antibodies, M30-specific T cells, tumor infiltrating cell population and tumor growth. Results Immunization with engineered EGFRvIII-OMVs induced a strong inhibition of tumor growth after B16F10EGFRvIII challenge. Furthermore, mice immunized with engineered OMVs carrying both EGFRvIII and M30 epitopes were completely protected from tumor challenge. Immunization was accompanied by induction of high anti-EGFRvIII antibody titers, M30-specific T cells and infiltration of CD4+ and CD8+ T cells at the tumor site. Conclusion OMVs can be decorated with tumor antigens and can elicit antigen-specific, protective anti-tumor responses in immunocompetent mice. The synergistic protective activity of multiple epitopes simultaneously administered with OMVs makes the OMV platform particularly attractive for cancer immunotherapy.